Creating and Sustaining customer value for UK luxury brands - Chhuon, Celine (2007)
The global market for luxury goods has witnessed a dramatic growth over the last 20 years. Traditionally bought by the Western elite they are now increasingly bought by middle- and lower-income earners as well as being sought by those in emerging Asian markets. For luxury brand owners there is a paradox inherent in the marketing of luxury goods, which reflects managers conflicting goals of striving to obtain high volume sales while maintaining exclusivity for their brands in the face of counterfeiting, parallel imports, overextensions and adoption of brands by inappropriate consumer groups. Little has been written by practitioners or academics on the marketing of luxury goods. Built on the strengths of existing theories (Smith and Colgate, 2007; Vigneron and Johnson, 1999) this study develops an understanding on the process of creating and sustaining customer value for luxury brands and provides a new framework for practitioners in order to develop more effective marketing strategies for British luxury brand owners.